Biotech on the Farm: Mississippi Agriculture in an Age of Proprietary Biotechnologies - Pechlaner, Gabriela (Anthropologica, 2022)
Agricultural biotechnologies have been introduced with a number of proprietary mechanisms: patents on seeds, grower contracts, incentive agreements and even litigation. Scholarly research on this proprietary framework’s impact on power relations in agriculture has primarily focused on devel? oping countries. This article draws on 40 interviews conducted in the agricultural community in Mississippi, United States, to investigate the technologies’ impact on agricultural production, and farmer’s response to this impact. I find that farmer’s con? trol over their production is reduced in important ways, limit? ing their opportunities for strategic response, but some acts of resistance in the legal forum are having a limited impact.